2014
DOI: 10.5114/ceji.2014.45951
|View full text |Cite
|
Sign up to set email alerts
|

Clinical immunology Impact on red blood cell immunity patterns in postoperative phase following total hip arthroplasty

Abstract: ObjectiveIn this study, we aimed to measure changes in red blood cell (RBC) immunity and cytokine levels after performing total hip replacement surgery.Material and methodsTwenty patients receiving total hip arthroplasty were investigated by measuring presurgical and postoperative RBC natural tumor erythrocyte rosette rate (NTERR), RBC C3b receptor rosette rate (RC3bRR), RBC membrane CD35, CD58 and CD59 expression and cytokine levels [including tumor necrosis factor α (TNF-α), interleukin 2 (IL-2), interferon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…These results also demonstrated that RBCs isolated from healthy individuals could be manipulated to alter their cytokine profile and their influence on T-cells. Similar dysregulation of RBC activity has been demonstrated in disease (carotid atherosclerosis) 6 , following surgery 7 , or following haemodialysis 41 . Further investigation around what causes this dysregulation in vivo and what role it may play in disease will be valuable.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…These results also demonstrated that RBCs isolated from healthy individuals could be manipulated to alter their cytokine profile and their influence on T-cells. Similar dysregulation of RBC activity has been demonstrated in disease (carotid atherosclerosis) 6 , following surgery 7 , or following haemodialysis 41 . Further investigation around what causes this dysregulation in vivo and what role it may play in disease will be valuable.…”
Section: Discussionsupporting
confidence: 60%
“…The role that RBCs play in modulating the activity of immune cells is now beginning to be reported 1,4,17 and a small number of papers have outlined how RBCs can become dysregulated in inflammatory conditions or following long term storage 7,20,21 . Our study aimed to build on these initial reports of RBCs derived from either healthy or disease cohorts by intentionally manipulating RBCs through co-culture with cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, erythrocyte CD44 and tumor cell surface hyaluronan may play a key role in erythrocyte adhesion to tumor cells and consequent development of inflammation and tumor metastasis. CD58, also known as lymphocyte functionassociated antigen-3 (LFA-3), is the natural ligand of the lymphocyte receptor CD2, which together forms the main costimulatory pathway for CD28 − CD8 + T cells in humans (Leitner et al, 2015;Yu et al, 2014). In particular, CD58 interacts with CD2 on the lymphocyte membrane to induce T lymphocytes to secrete cytokines, indirectly promoting T cell proliferation and differentiation (Antunes et al, 2011;Shivam et al, 2013).…”
Section: Introductionmentioning
confidence: 99%